2019
DOI: 10.5114/ceji.2019.87067
|View full text |Cite
|
Sign up to set email alerts
|

Associations of TRAF1/C5 rs10818488 and rs3761847 polymorphisms with genetic susceptibility to rheumatoid arthritis: a case-control study and updated meta-analysis

Abstract: The results on associations of tumor necrosis factor (TNF)-receptor associated factor 1/complement component 5 (TRAF1/C5) rs10818488 and rs3761847 polymorphisms with rheumatoid arthritis (RA) are controversial, thus this study was performed to examine whether the aforementioned polymorphisms were associated with RA in a Chinese population. Furthermore, an updated meta-analysis was conducted. The polymorphisms were genotyped in 328 Chinese RA patients and 449 healthy controls. Studies examining the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…23 Several single nucleotide polymorphisms (SNPs) of C5, such as rs10818488, rs3761847 and rs2269067, have been shown to be associated with the risks of various inflammation-related diseases, including systemic lupus erythematosus, rheumatoid arthritis, and proliferative diabetic retinopathy of type 2 diabetes. [24][25][26] Another functional SNP in our study, a missense rs17611 SNP leading to a V802I change in C5, is responsible for changes in C5a production, resulting in susceptibility to rheumatoid arthritis and ischemic stroke and poor prognosis of pneumococcal meningitis. [27][28][29] However, no current studies have explored the clinical relationship of C5 SNPs with the progression and clinical prognosis of sepsis.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…23 Several single nucleotide polymorphisms (SNPs) of C5, such as rs10818488, rs3761847 and rs2269067, have been shown to be associated with the risks of various inflammation-related diseases, including systemic lupus erythematosus, rheumatoid arthritis, and proliferative diabetic retinopathy of type 2 diabetes. [24][25][26] Another functional SNP in our study, a missense rs17611 SNP leading to a V802I change in C5, is responsible for changes in C5a production, resulting in susceptibility to rheumatoid arthritis and ischemic stroke and poor prognosis of pneumococcal meningitis. [27][28][29] However, no current studies have explored the clinical relationship of C5 SNPs with the progression and clinical prognosis of sepsis.…”
Section: Introductionmentioning
confidence: 83%
“…Recent studies identifying the responsible genetic variants have demonstrated that several C5 SNPs influence C5 mRNA expression and C5a production and confer susceptibility to various inflammatory diseases. [24][25][26][27][28][29] Xu et al found that the GG genotype of the C5 rs2269067 polymorphism resulted in elevated C5 expression and patient predisposition to acute anterior uveitis. 43 Other studies indicated that rs17611, a missense polymorphism leading to a V802I change in C5, was associated with elevated C5a production, increased susceptibility to large artery atherosclerosis stroke, and poor cardiovascular outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 remaining intronic SNVs (rs10463951) in transient receptor potential cation channel subfamily C member 7 gene (TRPC7), (rs6478300) (Wang et al, 2009) in astrotactin 2 gene (ASTN2), and (rs3761847) (Huang et al, 2019;Plenge et al, 2007) in TNF receptor associated factor 1 gene (TRAF1) are all reportedly related to the autoimmune disease rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to prevent RA at an early stage and reduce the subsequent disease burden, and this can be achieved by predicting the disease susceptibility to RA of individuals in advance based on an individual's genetic information. Large-scale GWAS studies and function analyses have identified many genetic variants [3] and risk genes [4] contributing to RA susceptibility [5][6][7][8], most of which are more likely in the HLA gene region [2,9]. In addition to genetic factors, RA is also affected by environmental factors.…”
mentioning
confidence: 99%